Discrete sound induced by low Mach number flow over side branch deep cavity in a rectangular duct - MEISSNER, M. (Archives of Acoustics, 1992)
This paper presents a model of the discrete sound induction effect due to a flow over a deep cavity in the wall of a rectangular duct. Theoretical analysis applies shear layer approximation with a vortex sheet, with deflection satisfying the Kutta-Żukowski condition, and an equivalent impedence system of a deep cavity with cavity impedence change in the presence of the flow included. The applied theoretical method makes it possible to determine the effect of resonance modes of the cavity on disturbances of the vortex sheet and also to determine the frequency and relative value of pressure amplitude in the case of a discrete sound.